Evaluation of the Implementation of the Affordable Housing Ownership Program in DKI Jakarta - Heru Andraiko (Monas: Jurnal Inovasi Aparatur, 2026)
The high backlog of home ownership in DKI Jakarta, which reached 1.2 million units in 2023, is a crucial issue that underlies the launch of the Affordable Owned Housing Program by the DKI Jakarta Provincial Government. However, the implementation of this program faces various obstacles such as complex regulations, funding, and administration. This research aims to comprehensively evaluate the implementation of the program, identify the obstacles faced, and formulate strategic recommendations. The research method used was a mixed qualitative and quantitative approach, which involved literature study, in-depth interviews with stakeholders, as well as the dissemination of questionnaires through online surveys to Beneficiaries. The results of the evaluation show that the Affordable Housing program has provided strategic benefits in overcoming the housing backlog, although there are various obstacles in implementation that need to be addressed. The survey results show that the majority of beneficiaries as much as 62.24% consider the credit repayment installments that must be paid to be lighter. But the survey results also show that as many as 81.63% of the beneficiaries experienced an increase in expenses after occupying a residence. This program has generally had a positive impact on the community, but it is necessary to simplify administrative procedures and improve coordination between stakeholders so that its implementation can be more optimal and sustainable.